Public policies and pollinator conservation: Implications for agricultural sustainability - Emilio José Medrano-Sánchez; Lourdes Sofia Cuenca-Silva (Trees, Forests and People, 2025)
The growing demand for agricultural products and intensive practices such as monocropping and pesticide use has put pollinators, essential to biodiversity and agricultural sustainability, at risk. This study examines public policies implemented between 2009 and 2024, evaluating their influence on pollinator conservation and highlighting challenges and opportunities to enhance their effectiveness. The research was conducted through a documentary review of 46 scientific articles sourced from the Scopus database. The results identified eight key thematic areas: ecosystem services, food security, protection policies, and economic valuation, among the most relevant, reflecting both achievements and areas for improvement in pollinator conservation. It concludes that the most effective policies are those that integrate scientific evidence with economic and social considerations. However, challenges such as excessive reliance on economic valuation in policy design and a lack of awareness persist. Therefore, a more holistic approach in future policies is recommended to ensure sustainable pollinator protection.